50 years of Historical Geography at the University of Costa Rica: evolution and trends in its teaching (1974-2024) - Sibaja Solís, Mario (2024)
The III University Congress marked the establishment of the Faculty of Social Sciences at the University of Costa Rica in 1973, along with the School of History and Geography. Since then, the course “Historical Geography” has been an integral component of the training of geography professionals. This paper reviews the topics, instructors, and conceptual proposals that have shaped the training in Historical Geography, aiming to discern the academic relevance of this field and the contributions of these trends to the professionalization of students in the geographical discipline.